Historical Processes and Contemporary Anthropogenic Activities Influence Genetic Population Dynamics of Nassau Grouper (Epinephelus striatus) within The Bahamas - Sherman, Krista D.; King, R. Andrew; Dahlgren, Craig P.; Simpson, Stephen D.; Stevens, Jamie R.; Tyler, Charles R. (Frontiers in Marine Science, 2017)
Severe declines of endangered Nassau grouper (Epinephelus striatus) across The Bahamas and Caribbean have spurred efforts to improve their fisheries management and population conservation. The Bahamas is reported to hold the majority of fish spawning aggregations for Nassau grouper, however, the status and genetic population structure of fish within the country is largely unknown, presenting a major knowledge gap for their sustainable management. Between August 2014–February 2017, 464 individual Nassau grouper sampled from The Bahamas were genotyped using 15 polymorphic microsatellite loci to establish measures of population structure, genetic diversity and effective population size (Ne). Nassau grouper were characterized by mostly high levels of genetic diversity, but we found no evidence for geographic population structure. Microsatellite analyses revealed weak, but significant genetic differentiation of Nassau grouper throughout the Bahamian archipelago (Global FST 0.00236, p = 0.0001). Temporal analyses of changes in Ne over the last 1,000 generations provide evidence in support of a pronounced historic decline in Bahamian Nassau grouper that appears to pre-date anthropogenic fishing activities. M-ratio results corroborate significant reductions in Ne throughout The Bahamas, with evidence for population bottlenecks in three islands and an active fish spawning aggregation along with apparent signs of inbreeding at two islands. Current estimates of Ne for Nassau grouper are considerably lower compared with historic levels. These findings represent important new contributions to our understanding of the evolutionary history, demographics and genetic connectivity of this endangered species, which are of critical importance for advancing their sustainable management.